The Influence Of Some Kind Of Zpt On The Growth Of Cuttings Stem Mulberry (Morus alba L.). - Diah Dwi Noviyanti; M Abror (Universitas Muhammadiyah Sidoarjo, 2019)
This study attempts to influence some kind of mengtahui ZPT on the growth of mulberry ( Morus alba L. ). The study is done for 2 months and November 2018 until January 2019. The research was done in Perum Mutiara Citra Asri Blok D4 no 4. This study using the random complete (RAL). That is the single factor concentration ZPT consisting of treatment 8 and each doses 2cc and 3cc covering ZPT chemical; extract onion; extract bean sprouts; excrescence bananas with three times repeat. Observation in this research include, time to germinate, long shoots, number of leaves, the number of roots, long roots, broad leaves, wet weight, and dry weights. Data analysis using anova followed by the BNJ 5%. The results of the study kind of natural and chemical ZPT influential on the growth of graft stems mulberry in treatment time to germinate, the number of shoots, long shoots, and number of leaves, but gave no the effect on treatment broad leaves, the number of roots, long roots, wet weight and weights dry.